If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -39 = 13 Reorder the terms: -39 + x = 13 Solving -39 + x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '39' to each side of the equation. -39 + 39 + x = 13 + 39 Combine like terms: -39 + 39 = 0 0 + x = 13 + 39 x = 13 + 39 Combine like terms: 13 + 39 = 52 x = 52 Simplifying x = 52
| 2x+4x-16-12b=24x+8-3x+6b | | 120+80= | | 10+x=48 | | 7x-6=23 | | 2-3x=6-5x | | x-7.6=-3.9 | | 6x-20+4x=180 | | 7(3x+5)=2(4x+13) | | w/3-4=1 | | 4(2+b)+(-2b)+-1-a-b=5 | | -7625+185x=12790 | | (2x-5)-(x+1)=10 | | 2x+5=7x-10 | | 7+5x=-3x+31 | | m/2-2=4 | | 56-x=5 | | 7x-6=3x+10 | | 6x-10=8-3x | | x/2+3=7 | | b-37=8 | | -4x-15=2x+21 | | y=-0.125x^2+1.375x+1.5 | | 3b+4.4=2.6+-6b | | -16y-8(3y-2)=-24 | | 11.7+-2x=x | | -2=h-7 | | (-3)3x-5=-y | | 15x^2+22+8=0 | | 11+2n=3n+6 | | (8i-14)+(2i-6)=90 | | 5(w)=11 | | 6(m)=12 |